Effects of Concrete Substrate Condition on Fiber-Reinforced Composite Strength Properties - Kiiru, Joseph; Kabubo, Charles; Sanewu, Fundi (Engineering, Technology & Applied Science Research, 2023)
This study determined the effects of concrete substrate conditions on the strength properties of fiber-reinforced composites through experimental research. The method of concrete surface preparation and moisture conditions were considered crucial parameters that have a significant impact on Fiber-Reinforced Composite (FRC) strength properties. Four different concrete surfaces were examined: grinded (CSP 2), sanded (CSP 3), scabbed (CSP 8), and unprepared (CSP 1), all under various moisture conditions: dry concrete substrate, saturated surface dry concrete substrate, and wet concrete substrate. A mix design conforming to the C25 grade concrete was formulated, cured in water for 7 and 28 days to achieve the desired design strength values. The dry surface specimens were cured in the air for at least 24 hr before subsequent preparations, the wet surface specimens were cured in water for at least 24 hr, while the saturated surface dry specimens were cured in water for 24 hours and then removed from the water and cured in the air for 1 hr. The prepared samples were carbon-wrapped with unidirectional SikaWrap-300 C and Sikadur 300 resin and then subjected to a uniaxial compressive strength test until failure after 24 hr of curing using a load of 0.2 MPa/sec. The collected data showed that the surface roughness of the CSP 8 under wet moisture conditions exhibited the best bond strength due to the increase in surface area for adhesive bond contact, while the wet substrate condition increased hydration on the adhesive side of the interface, which directly contributed to the increase in bond strength. All substrate conditions demonstrated cohesive cracking of the concrete substrate leading to displacement of the FRP-concrete interface before FRP rapture.